2017
DOI: 10.1080/10408444.2017.1391746
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the evidence on genotoxicity and reproductive toxicity of carbon black: a critical review

Abstract: Carbon black is produced industrially by the partial combustion or thermal decomposition of gaseous or liquid hydrocarbons under controlled conditions. It is considered a poorly soluble, low toxicity (PSLT) particle. Recently, results from a number of published studies have suggested that carbon black may be directly genotoxic, and that it may also cause reproductive toxicity. Here, we review the evidence from these studies to determine whether carbon black is likely to act as a primary genotoxicant or reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 118 publications
(172 reference statements)
1
27
0
Order By: Relevance
“…The mechanism of cell damage by nanodiamonds is by generating ROS, and by excessive delivery of sodium ions adsorbed on the nanodiamond surface [168]. Last but not least, carbon nanoparticles can be immunogenic, i.e., they can activate inflammatory reactions, which can be, as has been demonstrated on carbon black, the main pathogenic mechanism of respiratory, cardiovascular and other serious diseases [166,167].…”
Section: Potential Cytotoxicity and Immunogenicity Of Nanocellulose/nmentioning
confidence: 98%
See 1 more Smart Citation
“…The mechanism of cell damage by nanodiamonds is by generating ROS, and by excessive delivery of sodium ions adsorbed on the nanodiamond surface [168]. Last but not least, carbon nanoparticles can be immunogenic, i.e., they can activate inflammatory reactions, which can be, as has been demonstrated on carbon black, the main pathogenic mechanism of respiratory, cardiovascular and other serious diseases [166,167].…”
Section: Potential Cytotoxicity and Immunogenicity Of Nanocellulose/nmentioning
confidence: 98%
“…Although it is considered to have low toxicity, the International Agency for Research on Cancer has classified it as possibly carcinogenic to humans. In addition, as a component of environmental pollution, carbon black can cause oxidative damage and an inflammatory reaction, which further mediate genotoxicity, reproductive toxicity, neurotoxicity and diseases of the respiratory and cardiovascular systems [166,167]. Nevertheless, carbon black is currently used as a filler in tires and in other rubber products, and as a pigment in inks, paints and plastics.…”
Section: Composites Of Nanocellulose and Carbon Blackmentioning
confidence: 99%
“…While they are generally not considered as high‐toxicity materials, rodent studies have clearly shown that nanosized carbon particles are far from completely inactive, being able to instigate both oxidative stress and inflammation. [ 94–97 ] However, such effects are often seen at very high doses associated with lung overload with considerable debate as to whether or not such effects are species specific and therefore of relevance to humans. [ 96 ]…”
Section: Controlled Exposures In Human Volunteersmentioning
confidence: 99%
“…Two pieces of information related to the toxicity of Super P carbon were found in literature. Chaudhuri et al [388] considered a carbon black (Super P) as a poorly soluble, weak toxicity (PSLT) particle. However, carbon black may be directly genotoxic, and is also able to induce reproductive toxicity.…”
Section: Separatorsmentioning
confidence: 99%